Assessment of cross-cultural adaptations and measurement properties of self-report outcome measures in Portuguese relevant to temporomandibular disorders: a systematic review - Letícia Miranda Resende da Costa; Daiane Lazzeri de Medeiros; Lilian Gerdi Kittel Ries; Audria Beretta; Marcos Amaral de Noronha (Universidade de São Paulo, 2014)
The aim of this study was to identify, through a systematic review, which questionnaires used to assess temporomandibular (TMD) disorders are available in the Portuguese language, describing and analyzing the procedures used to translate and adapt the questionnaire into Portuguese, as well their measurement properties. Systematic searches were performed in five electronic databases (MEDLINE by PubMed, Embase, CINAHL by EBSCO, SciELO and LILACS). All studies were analyzed according to the criteria of quality guidelines for the procedures for cross-cultural adaptation and measurement properties. There were 1.418, of which only six were eligible. Manual search retrieved two additional articles and a book chapter, totaling nine eligible studies. Four instruments were translated/adapted into Portuguese: The Research Diagnostic Criteria for Temporomandibular Disorders: Axis II (RDC/TMD); the Fonseca Questionnaire and Anamnestic Index; the Questionnaire from the American Academy of Orofacial Pain (QAADO); and Mandibular Function Impairment Questionnaire (MFIQ), but none of these questionnaires where fully submitted to the steps for translation and adaptation recommended by the followed guidelines and none of the questionnaires had all measurement properties tested. The RDC/TMD and tehe MFIQ are the best available questionnaires in Portuguese to assess TMD, as were those with the most measurement properties acceptable results tested.